Analisis Ujaran Kebencian dalam Komentar Warganet terhadap Inara Rusli pada Akun Podcast Denny Sumargo (@CURHAT Bang Denny Sumargo) dalam Perspektif Linguistik Forensik - Haniyah Kamilah Az-Zahra; Hari Windu Asrini (Pusat riset dan Inovasi Nasional, 2026)
The rapid development of social media has expanded public interaction while increasing the occurrence of hate speech in digital communication. This study examines hate speech directed at Inara Rusli in the comment section of Denny Sumargo’s podcast account (@CURHAT Bang Denny Sumargo). It aims to identify the forms of speech acts used in hate speech and analyze the types of hate speech along with their linguistic indicators from a forensic linguistics perspective. This research employed a qualitative descriptive approach. Data consisted of netizens’ comments containing hate speech, collected through observation, reading, and note-taking techniques. The data were analyzed using the interactive analysis model involving data reduction, data display, and conclusion drawing. Speech act analysis was based on John Searle’s (1979) Speech Act Theory, while hate speech was examined using forensic linguistics. The findings reveal three forms of speech acts, namely expressive, directive, and assertive, with expressive speech acts dominating in the form of criticism, blame, and condemnation. Four types of hate speech were identified: insult, defamation, provocation, and stigmatization. These were realized through words, phrases, and sentences containing pejorative lexical items, negative labeling, accusations, and imperative constructions. The study concludes that these linguistic features function as linguistic evidence representing speakers’ attitudes while constructing negative public images of the target, contributing to the development of forensic linguistics research on hate speech in social media.